2022
DOI: 10.21522/tijph.2013.10.03.art017
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Facilitators of High Viral Load in HIV Positive Persons on Antiretroviral Treatment in the East Region of Cameroon

Abstract: Viral load (VL) determination is the standard to assess the effectiveness of Anti-retroviral Therapy (ART) in people living with HIV (PLWIV). According to Cameroon national ART guidelines, VL determination in PLHIV should be done after six months of starting ART and then every 12 months. Unsuppressed VL occurs when ARV’s fails to suppress viral load and is associated with decreased survival and increased risk of HIV transmission, morbidity, and mortality. A sequential and exploratory facility and community-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
(20 reference statements)
2
2
0
Order By: Relevance
“…Occupation at initiation was a significant predictor of viral load suppression, with farmers exhibiting statistically significant lower odds of unsuppressed viral load compared to the unemployed. This result aligns with a study conducted in Cameroon [20] and in a similar African setting [22], highlighting the impact of occupation on treatment outcomes. The unique challenges faced by different occupational groups, such as workrelated stressors or scheduling conflicts, may contribute to these disparities.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Occupation at initiation was a significant predictor of viral load suppression, with farmers exhibiting statistically significant lower odds of unsuppressed viral load compared to the unemployed. This result aligns with a study conducted in Cameroon [20] and in a similar African setting [22], highlighting the impact of occupation on treatment outcomes. The unique challenges faced by different occupational groups, such as workrelated stressors or scheduling conflicts, may contribute to these disparities.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning the behavioral and clinical factors influencing viral suppression, we found that individuals whose partners were informed of their HIV status had statistically significant lower odds of unsuppressed viral load compared to those who did not disclose, suggesting a consistent pattern across diverse settings [21]. The results of our study align with findings from Cameroon [20] and United Kingdom [22], emphasizing the crucial role of partner disclosure in achieving viral load suppression. This underscores the need for tailored interventions that promote open communication within relationships to enhance treatment outcomes.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations